The Role of Human Capital in Ensuring Food Security of the Region - SERGEEVNA, Gorbunova Olesya; ALEKSANDROVICH, Voronin Boris; IVANOVNA, Bukhtiyarova Tatyana; VLADIMIROVNA, Zyryanova Tatyana; NIKOLAEVICH, Mitin Alexander; GERMANOVICH, Mokronosov Alexander (Journal of Environmental Management and Tourism, 2020)
Food security can be assessed as providing the population with food for their comfortable and safe life.After all, eat a wholefood diet, healthy person has high labor productivity, the ability to accumulate his knowledge, skills, the ability to develop and self-develop, namely a high level of human capital.Thus, we see the relationship between food security and the formation of human capital and vice versa.The main aim of the study and its novelty was the analysis of the identified main factors and the determination of the role of human capital in food security of the Sverdlovsk region.